2012
DOI: 10.1016/j.ajic.2011.10.013
|View full text |Cite
|
Sign up to set email alerts
|

“Swimming in resistance”: Co-colonization with carbapenem-resistant Enterobacteriaceae and Acinetobacter baumannii or Pseudomonas aeruginosa

Abstract: Background Co-colonization of patients with carbapenem-resistant Enterobacteriaceae (CRE) and Acinetobacter baumannii (AB) or Pseudomonas aeruginosa (PA) is reported to be associated with increased antibiotic resistance and mortality. Methods CREs isolated between September 2008 and September 2009 were analyzed at Detroit Medical Center. Patients who had an additional isolation of AB or PA during the period spanning 7 days before to 7 days after CRE isolation were considered co-colonized. Molecular typing wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 23 publications
3
57
1
Order By: Relevance
“…Interestingly, Marchaim et al, also found that previous therapy with antimicrobials with solely Gram-positive spectra was significantly associated with co-colonisation of patients with CRE, CRAb and CRPa. Likewise, in our study, the clinical history (data not shown) of patients shows that all four patients were also treated with vancomycin post-surgery, supporting the Marchaim et al's suggestion that suppression of the Gram-positive flora in these patients may have facilitated the acquisition of opportunistic infections with MDR Gram-negative organisms [21].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Interestingly, Marchaim et al, also found that previous therapy with antimicrobials with solely Gram-positive spectra was significantly associated with co-colonisation of patients with CRE, CRAb and CRPa. Likewise, in our study, the clinical history (data not shown) of patients shows that all four patients were also treated with vancomycin post-surgery, supporting the Marchaim et al's suggestion that suppression of the Gram-positive flora in these patients may have facilitated the acquisition of opportunistic infections with MDR Gram-negative organisms [21].…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies have also suggested that Acinetobacter infections are associated with increased morbidity and mortality [18][19][20]. In addition, Marchaim et al, found that cocolonisation with carbapenem-resistant Enterobacteriaceae (CRE), CRAb and/or CRPa was the strongest independent predictor for 90-day mortality [21]. These features can also be recognised in our study, where three patients co-infected/ colonised with ColRKp, CRPa and/or CRAb died, whilst the fourth patient with a mono-microbial K. pneumoniae infection survived.…”
Section: Discussionmentioning
confidence: 94%
“…Co-colonization of patients with carbapenem-resistant Enterobacteriaceae and A. baumannii or P. aeruginosa has been shown to be associated with increased antibiotic resistance and mortality (10). As potential interspecies interactions may enhance bacterial virulence and antibiotic resistance, co-colonization or co-infection of patients with the intrinsically carbapenem-resistant S. maltophilia and A. baumannii or P. aeruginosa might be associated with increased antibiotic resistance and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…usually XDR pathogens), but could also result from MDR pathogens of the same species as well (i.e. ampicillinresistant vancomycin-susceptible enterococci, ESBL-producing enterobacteriaceae, carbapenem-susceptible A. baumannii or carbapenem-susceptible P. aeruginosa) [3].…”
Section: Prediction Scoresmentioning
confidence: 99%
“…Certain MDR, XDR and PDR organisms (to be referred to collectively as MDROs), in certain regions, have become prevalent pathogens [3], and some successfully have spread to community settings as well [4][5][6][7][8][9][10][11]. The IDSA formulated an acronym ESKAPE, in order to emphasize the group of pathogens that cause hospital infections and effectively "escape" the effects of antibacterial drugs.…”
Section: Epidemiology Of Multidrug Resistant Organismsmentioning
confidence: 99%